1999
DOI: 10.1038/sj.ejcn.1600829
|View full text |Cite
|
Sign up to set email alerts
|

Diet in relation to socioeconomic status in patients with coronary heart disease

Abstract: Objectives: Nutrient intake, food consumption and fatty acid pro®le of serum cholesteryl esters (CE) were investigated in relation to education in patients with coronary heart disease (CHD). Design: A cross-sectional survey in CHD patients selected from hospital records at least six months after hospitalisation. Food record, a questionnaire on dietary fat and fatty acid pro®le of CE were used to examine diet composition. Years of education, divided into three categories, were used to indicate socioeconomic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
7
18
0
Order By: Relevance
“…n 1 : number of studies by educational level; n 2 : number of studies by occupational level. Our findings about a higher consumption of cheese in the higher social class are consistent with previous studies (Popkin et al, 1989;Erkkilä et al, 1999;Borrell et al, 2000). We also observed a positive association between a higher level of education and a greater consumption of milk.…”
Section: Socioeconomic Differences In Food Habits In Europesupporting
confidence: 93%
See 2 more Smart Citations
“…n 1 : number of studies by educational level; n 2 : number of studies by occupational level. Our findings about a higher consumption of cheese in the higher social class are consistent with previous studies (Popkin et al, 1989;Erkkilä et al, 1999;Borrell et al, 2000). We also observed a positive association between a higher level of education and a greater consumption of milk.…”
Section: Socioeconomic Differences In Food Habits In Europesupporting
confidence: 93%
“…Many studies have reported social differences in food consumption as well as the quantity and quality of the diet composition (Erkkilä et al, 1999;Fraser et al, 2000;Hupkens et al, 2000). On average, a higher socioeconomic level has been associated with healthier dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedentary lifestyle (47,48) , smoking habit (47,48,50) , low educational level and social class (3,42,51,52) and low adherence to the Mediterranean diet are factors that often accompany unhealthy lifestyles. The positive association we detected between physical activity and Mediterranean diet adherence is noteworthy in this context, suggesting that public health or preventive interventions must address diet and physical activity in conjunction.…”
Section: Discussionmentioning
confidence: 99%
“…Plant and animal origin food should be consumed as required by the metabolism for completion of physiological needs (Onurlubaş, 2011). Although, according to most studies on the socio-economically high income group, a healthy diet is considered to be one containing more fruit and vegetable and less fat and meat (Roos et al, 1996;Erkkila et al, 1999;Irala-Estevez et al, 2000;Villegas et al, 2003) 40-50% of the protein need should be of animal origin in a healthy and wellbalanced nutrition. Meat plays significant share among the animal origin protein sources.…”
Section: Introductionmentioning
confidence: 99%